KRAS pathway and mutations in cancer - Tanaka, Kayoko (Henry Stewart Talks, 2025)
Ras family of small GTPases, Ras acts as a molecular switch, Oncogenic mutations in KRAS, Effect of endogenous and overexpressed KRAS, Raf-MEK-ERK signalling axis, KRAS-Rgl2-RalA/B signalling axis is mediates oncogenic Ras signalling